Current Management of Pesticides Wastes in Some Cultivating Models in Vietnamese Mekong Delta (Research Centre of Inorganic Materials and Complexs, 2022)
The study was carried out to evaluate the current status of use and management of waste from pesticides on some farming models in the Mekong Delta through interviews with 140 households cultivating triple-rice, Durian Ri6 and E-dor longan. The results of the study showed that 130 types of pesticides and 99 active ingredients were used on three farming models. The study also discovered that five banned active ingredients are still used in the triple-rice practice and four banned substances in the Durian Ri6 cultivation. The proportions of toxic groups (according to WHO’s classification) at levels II, III, IV were 33.3%, 29.3% and 37.4%, respectively. The triple-rice crop model used the most pesticides, but the frequency of spraying was only in the range of 6.48±1.72 to 7.33±1.82 times/crop. Meanwhile, the Durian Ri6 model, although using fewer pesticides, the frequency of spraying was very high (about 61.8±9.1 times/crop), 9 times higher than a rice crop. The cultivation of E-dor longan uses the least amount of pesticides as well as a very low frequency of spraying. The methods of handling pesticidal wastes are mainly burning, burying and these practices are not meeting the requirements for protecting health and the environment. The study provides important information for decision-making to choose a farming model and the accompanying environmental protection solutions to minimize the adverse effects of the use of pesticides.